Analisa Keausan Mata Pahat Kardiba dan Kedalaman Potong pada Proses Milling Baja SKD 11 - Hidayat, Ega Prasetya; Lubis , Sobron Yamin; Rosehan, Rosehan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Not all machining processes are carried out using a CNC (Computer Numerical Control) system, but are started by using conventional machines that do not require a high level of accuracy. In accordance with the advantages it has for product accuracy, most CNC systems are intended for finishing processes. The level of surface roughness of a product is indeed adjusted to the usefulness of the product itself, but it cannot be denied that the better the quality produced, the higher the selling value of the product. This study aims to determine the effect of variations in depth of cut on the wear value of the EndMill Carbide chisel on the SKD 11 steel material used in the manufacture of Dies. This study used a literature study type method, research procedures, first material preparation, second specimen machining procedure, recorded cutting time, looked at the surface of the tool after the cutting process was carried out using a microscope, determined the condition of the tool damage and then re-cut until the tool could not be used again or wear has reached 0.3 mm, then record the cutting length every 5 minutes of cutting and finally data analysis. Based on the results of the test data obtained, it shows that the wear of the carbide endmill (VB) chisel blade from the comparison of machining time and feed rate has a graph, namely if the cutting time is longer, namely 30 minutes. The higher the cutting length, the faster the wear value occurs and vice versa the lower the cutting length value, the smaller the wear value achieved. The type of endmill carbide cutting tool wear that occurs is flank wear.